Magnetic Resonance Imaging Findings in Kallmann Syndrome: 14 Cases and Review of the Literature. Issue 1 (January 2016) - Zhang, Zengfang; Sun, Xiaolin; Wang, Cuiyan; Wang, Guangbin; Zhao, Bin
Abstract : Purpose: We sought to characterize the magnetic resonance imaging (MRI) findings in patients with Kallmann syndrome (KS). Materials and Methods: Fourteen patients with KS and a comparison group of 20 matched people with normal MRI were analyzed with optimized voxel-based morphometry. Coronal T1- and T2-weighted images from the anterior margin of the frontal sinus to the hypothalamus were obtained. The olfactory sulci, bulbs, and bundles were assessed as normal, hypoplastic, or absent. The pituitary gland was also evaluated. Results: Four of the 14 patients came from 1 family. Ten patients had low levels of GnRH and gonadal hormone, 11 had hyposmia, and 3 had anosmia. On MRI, the olfactory bulbs (OBs) and bundles were absent bilaterally in 8 patients. Two patients exhibited absence of the OBs and bundles on the left and hypoplasia on the right. Four patients displayed bilateral hypoplastic OBs and bundles. The olfactory sulci were absent in 5 and hypoplastic in 9 of these patients. The anterior pituitary was hypoplastic in 6 patients. Conclusions: Kallmann syndrome has distinctive features on MRI. Magnetic resonance imaging may aid in the diagnosis of KS in patients with ambiguous clinical findings.